1984
DOI: 10.1093/jnci/73.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B Potentiation of the Cytotoxicity of Anticancer Agents Against Both Normal Hematopoietic and Leukemia Cells in Mice2

Abstract: Dose-response curves in AKR or CD2F1 mice were obtained for AKR leukemia, L1210 leukemia, and hematopoietic stem cells following in vivo administration of one of the following anticancer agents alone or in combination with amphotericin B (AmB): doxorubicin, lomustine, or melphalan. AmB potentiated drug cytotoxicity of all agents against both leukemias. Potentiation of all three agents was greatest with the AKR leukemia demonstrating dose-modifying factor (DMF) values of 1.8, 3.0, and 2.7, respectively, for lom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Each conformation is characterized with a unique spatial organization of the chemical groups involving in non-covalent bonding. This structural plasticity creates a vast variety of bioactivities of these compounds, but makes the structureactivity relationship modelling rather difficult [13,42]. Moreover, a recent study reported a keto-enolic tautomerization of batumin that increases significantly the number of possible conformations of this compound [25].…”
Section: Discussionmentioning
confidence: 99%
“…Each conformation is characterized with a unique spatial organization of the chemical groups involving in non-covalent bonding. This structural plasticity creates a vast variety of bioactivities of these compounds, but makes the structureactivity relationship modelling rather difficult [13,42]. Moreover, a recent study reported a keto-enolic tautomerization of batumin that increases significantly the number of possible conformations of this compound [25].…”
Section: Discussionmentioning
confidence: 99%
“…It binds to ergosterols of fungal cell membranes and—with lower affinity—to sterols of mammalian plasma membranes (40–42). Amphotericin B forms discrete pores that make membranes permeable to ions and small molecules such as doxorubicin, cisplatin and carboplatin (43–49). Amphotericin B has been used successfully to overcome drug resistance in preclinical models of cancer (43–49).…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B forms discrete pores that make membranes permeable to ions and small molecules such as doxorubicin, cisplatin and carboplatin (43–49). Amphotericin B has been used successfully to overcome drug resistance in preclinical models of cancer (43–49). The results of clinical trials, however, have been disappointing, with amphotericin B failing to reverse drug resistance in the majority of cases (50).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, amphotericin has been demonstrated to enhance the intracellular penetration of anticancer agents into leukemic cells without affecting the penetration into normal hematopoietic stem cells in a number of in vitro models [1][2][3][4]. The time course and clinical significance of this phenomenon remains to be determined, so no clinical recommendations can be made at this time.…”
Section: Polyenesmentioning
confidence: 99%